Oral health assessment in pregnant women: An observational study - Shailesh Kumar (Bioinformation, 2026)
Oral hygiene and its negative impact on pregnancy are often ignored in underdeveloped countries. Maintaining oral health throughout pregnancy is crucial because failing to do so may result in low birth weight and preterm birth. Therefore, it is of interest to evaluate the dental hygiene of expectant mothers throughout a six-month period. The most common dental problems in our study were bleeding gums (20.5%) and toothache (35.4%). Thus, data shows a significant effort should be made to improve the knowledge and attitude of pregnant women towards dental health.